Pemetaan Wacana Berbasis Korpus di Media Sosial - Dian Rousta Febryanti; Ibnu Hamad; Udi Rusadi (Jurnal ILMU KOMUNIKASI, 2024)
The #MeToo hashtag grew into digital activism among the Twitter users. This activity was becoming the networking space which increased the communication power and collaboration. This research using counter public and the fifth estate as a frame for thinking with a method of social media analyses and critical discourse based on corpus. The object of this research is 631,897 tweets of #MeToo from October 15, 2017 until March 31, 2020. The result shows there is no counter public through this hashtag for the Indonesian context. Nevertheless, users applied the social control for legitimacy of laws and sexual abuse legal cases.